Hipersuperfícies de curvatura média constante folheadas por esferas - Butta, André Pizzaia (2008)
This MSc will explore hypersurfaces n-dimensional (lines) in Euclidean space Rn +1 and in the hyperbolic space Hn +1. Consider that the hypersurfaces have constant mean curvature and are plated by (n-1)-hyperspheres. We will need results classics as Alexandrov's theorem and a theorem of symmetry. Basically answer the following question: When a hypersurface of dimension n with constant mean curvature and sliced by a ball in the space above is a hypersurface of revolution? Moreover, in Rn +1 the spheres will be contained in parallel hyperplanes and in horoesferas Hn +1.